Antiretroviral concentration measurements as an additional tool to manage virologic failure in resource limited settings: a case control study - Buzibye, Allan; Musaazi, Joseph; Braun, Amrei von; Nanzigu, Sarah; Sekaggya‑Wiltshire, Christine; Kambugu, Andrew; Fehr, Jan; Lamorde, Mohammed; Gutteck, Ursula; Muller, Daniel; Sowinski, Stefanie; Reynolds, Steven J.; et al. (AIDS research and therapy, 2019)
Several studies demonstrate a correlation between sub-therapeutic concentrations of antiretroviral drugs and virologic failure. We examined the sensitivity, specificity and predictive values of sub-therapeutic drug levels in predicting viralogic failure. Methods: This was a case control study with cases being samples of participants with virologic failure, and controls samples of participants with virologic suppression. We analyzed samples obtained from participants that had been on antiretroviral treatment (ART) for at least 6 months. Virologic failure was defined as HIV-RNA viral load ≥ 1000 copies/ ml. Sub-therapeutic drug levels were defined according to published reference cutoffs. The diagnostic validity of drug levels for virologic failure was assessed using plasma viral loads as a gold standard. Results: Sub-therapeutic ART concentrations explained only 38.2% of virologic failure with a probability of experiencing virologic failure of 0.66 in a patient with low drug levels versus 0.25 for participants with measurements within or above the normal range. Approximately 90% of participants with ART concentrations above the lower clinical cut off did not have virologic failure. Conclusions: These results support prior indication for therapeutic drug monitoring in cases of suspected virologic failure.
Keywords: Virologic failure; Therapeutic drug monitoring; Resource limited setting; HIV